RECOMMENDATION FOR DISASTER MITIGATION THROUGH THE ANALYSIS OF INDONESIAN NOVELS - Eva Dwi Kurniawan; Septi Riana Dewi (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
Disaster becomes a phenomenon that cannot be separated from human life. The increasing intensity of disasters recently signaled that readiness to face the impact of disasters must be increased. Many Indonesian novels provide implied and explicit recommendations regarding disaster mitigation. This study analyzes the recommendations presented in Indonesian novels. The method used in this research is structural. The findings obtained from this study are the recommendation for disaster mitigation in the fields of technology, social, religion and transportation.